Unified tactile detection and localisation in split-brain patients. (March 2020) - de Haan, Edward H.F.; Fabri, Mara; Dijkerman, H. Chris; Foschi, Nicoletta; Lattanzi, Simona; Pinto, Yair
Abstract: In 'split-brain' patients, the corpus callosum has been surgically severed to alleviate medically intractable, severe epilepsy. The classic claim is that after removal of the corpus callosum an object presented in the right visual field will be identified correctly verbally and with the right hand but not with the left hand. When the object is presented in the left visual field the patient verbally states that he saw nothing but nevertheless identifies it accurately with the left hand. This interaction suggests that perception, recognition and responding are separated in the two isolated hemispheres. However, there is now accumulating evidence that this interaction is not absolute. Recently, we (Pinto et al., 2017) showed that accurate detection and location of stimuli anywhere in the visual field could be performed with both hands. In this study, we explored detection and localisation of tactile stimulation on the body. In line with our previous results, we observed that split-brain patients can signal detection and localisation with either hand anywhere on the body (be it the arm or the leg) but they remain unable to match positions touched on both arms or legs simultaneously. These results add to the evidence suggesting that the effects of removal of the corpus callosum may be less severe than sometimes claimed.